Sistema para la Monitorización de Frecuencia Cardíaca y Respiratoria Mediante Cámara Web - Barajas González, E.; Cabello Gómez, F.; Campos Gutiérrez, J. A.; Gutiérrez Zermeño, M. (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
Remote monitoring provides new opportunities to evaluate the condition of patients without the need for electrode or sensor placement. In the present work, different techniques for signal conditioning image photoplethysmography are integrated to calculate the heart and respiratory rates through video recording. In addition, a system is proposed that allows the tracking and monitoring of patients remotely using a web camera. The results show a high precision between the measurement recorded by the proposed application and the reference devices used.